2009
DOI: 10.1007/s11104-009-9920-5
|View full text |Cite
|
Sign up to set email alerts
|

Linking plant morphological traits to uprooting resistance in eroded marly lands (Southern Alps, France)

Abstract: In marly catchments of the French Southern Alps, soils are subjected to harsh water erosion that can result in concentrated flows uprooting small plants. Evaluating and predicting plant resistance to uprooting from simple plant traits is therefore highly important so that the most efficient plant strategy for future restoration of eroded slopes can be defined. Twelve species growing on marly land were studied. For each species, in-situ lateral uprooting tests were conducted and morphological plant traits were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
55
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 45 publications
10
55
0
1
Order By: Relevance
“…Concentrated runoff loaded with sediment can uproot established plants that could have stabilized the slopes (Burylo et al 2009). Therefore, it is important to quantify and predict the soil-reinforcing ability of plant roots as well as their resistance to external loads such as wind and debris flow.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concentrated runoff loaded with sediment can uproot established plants that could have stabilized the slopes (Burylo et al 2009). Therefore, it is important to quantify and predict the soil-reinforcing ability of plant roots as well as their resistance to external loads such as wind and debris flow.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the mechanisms of root anchorage in artificial regeneration systems (Ennos 1990, Stokes et al 1996, Bailey et al 2002 and naturally established plants (Karrenberg et al 2003, Devkota et al 2006) have focused on vertical uprooting. Stokes et al (2007) used a lateral pulling test to simulate plant failure during a landslide, whereas other researchers used this method to estimate root resistance when torrential runoffs and sediments are in the process of uprooting the plants (Mickovski 2005, Burylo et al 2009.…”
Section: Introductionmentioning
confidence: 99%
“…Dupuy et al (2005) indicated that rooting depth was a determinant factor of tree anchorage in sandy soils. Burylo et al (2009) showed that the maximum uprooting force is most positively correlated with stem basal diameter and taproot length is the best predictor of anchorage strength. Liu et al (2013) showed that uprooting resistance of Chinese willow (Salix matsudana Koidz) was significantly positively correlated with plant height, total number of roots and root biomass.…”
Section: Root Anchorage Capabilitymentioning
confidence: 97%
“…Then, roots and stems were dried in an oven at 75°C till constant weight for biomass measurement. Root functional traits, that is, root mass density (RD in kg m -3 , root dry mass per unit volume of soil), root length density (RLD in km m -3 , root length per unit volume of soil), root tissue density (RTD in g cm -3 , root dry mass per unit volume of root), specific root length (SRL in m g -1 , root length per unit root dry mass), and root to shoot ratio (R/S, dry root mass divided by dry leaf and shoot mass) were calculated (Stokes et al, 2009;Burylo et al, 2009Burylo et al, , 2012Poorter et al, 2012;Gould et al, 2016). All root traits were pooled together and analyzed.…”
Section: Growth and Root System Morphologymentioning
confidence: 99%
“…The progress made during the past few years on the contribution of the root system in reinforcing mass-stability of slopes is an eye-opener. Soil cover with grass or herbaceous vegetation provides an efficient protection against surface erosion by reducing the impact of rainfall on bare soil (Davide et al, 2000), besides increased percolation of water, soil cohesion, and resistance on the banks, which are provided by the root systems (Burylo et al, 2009). Cazzuffi et al (2006) mentioned that vetiver grass (Vetiveria zizanioides L. Nash) among other species is characterized by very resistant roots and confirms how they, could be successfully used with stabilizing effects on phenomena like shallow instability ( Figure 3).…”
Section: Erosion Control Blanketmentioning
confidence: 99%